PELATIHAN PENCATATAN DAN MANAJEMEN KEUANGAN KELUARGABAGI KELOMPOK PENGAJIAN / PKK RT 006 RAJABASA RAYA - Nurmala, - -; Damayanti, - - (IBI Darmajaya, 2015)
Recitation of PKK RT 006 Rajabasa Raya is a group of mother-housewife that have PKK activity andstudy qurâan in their daily activities. As a wife, they control all money for their family that they have, fromregular or unregular income and regular and unregular ekspenses. The topic issues of them are how to managetheir financial at over budget post thatcauses they have defisit condition in last month. Family financialstatements, is a process of manage money to achieve financial goals. Benefits of financial statements is to knowabout the expenditure of money and how much their income dan expenses. The methods used in this trainingare counseling, simulation / demonstration and mentoring. This training of 35 participant can create familyfinancial management, beside that mother-housewife have the better knowledge and understanding thanbefore. The fact is Participants of training have financial letter in September 2013. The expected after thistraining is participant still consistent to records they financial activity, therefor have a good family financialmanagement to realizing a prosperous familyKeywords: Training, family financial statements, family financial management, the motherhousewife